(untitled) (LEARNing Landscapes, 2015)
Teacher researchers live at the overlap of theory and practice, consciously inhabiting dual worlds of thought and action. Using a poetic form, the author reflects on her roles as both teacher and student to comment on the pleasurably paradoxical structure and freedom involved in the inquiry process. By explaining the creation of her ode to practitioner inquiry within the parameters of the villanelle form, she embraces the significance of the process alongside the product, valuing both elements as vital for truly reflective practice.